MODELING FUTURE GLACIER MASS BALANCE AND VOLUME CHANGES USING ERA-40 REANALYSIS AND CLIMATE MODELS: A SENSITIVITY STUDY AT STORGLACIäREN, SWEDEN - Radić V.; Hock R. (My University, 2006)
Modeling the response of glaciers to future climate change is important for predicting changes in global sea level rise and local water resources. We compute until the year 2100 the mass balance and volume evolution of Storglaciären, a small valley glacier in Sweden, using a temperature index mass balance model. We focus on the sensitivity of results to the choice of climate model and variants of adjusting ERA-40 temperatures to local conditions. ERA-40 temperature and precipitation series from 1961 to 2001 are validated and used both as input to the mass balance model and for statistical downscaling of one regional and six global climate models (GCMs). Future volume projections are computed using area-volume scaling and constant glacier area. ERA-40 data correlate well with observations and capture observed interannual variability of temperature and precipitation. The mass balance model driven by several variants of ERA-40 input performs similarly well regardless of temporal resolution of the input series (daily or monthly). The model explains ~70% of variance of measured mass balance when the input temperatures are reduced by the lapse rate that maximizes model performance. Fitting ERA-40 temperatures to observations close to the glacier does not improve the performance of the model, leading us to conclude that ERA-40 can be used for mass balance modeling independent of meteorological observations. Projected future volume series show a loss of 50-90% of the initial volume by 2100. The differences in volume projections vary by 40% of the initial volume for six different GCMs input to mass balance model, while each volume projection varies by 20% depending on whether volume-area scaling or constant area is used and by 10% depending on details in the mass balance model used. The correction of biases in the seasonal temperature cycle of the GCMs with respect to the ERA-40 data is crucial for deriving realistic volume evolution. Static mass balance sensitivities to temperature and precipitation change in the 21st century are -0.48 in yr-1 K-1 and 0.025 m yr-1 per % increase, respectively. Copyright 2006 by the American Geophysical Union.